First-line pemetrexed plus cisplatin followed by gefitinib maintenance therapy versus gefitinib monotherapy in East Asian patients with locally advanced or metastatic non-squamous non-small cell lung cancer: A randomised, phase 3 trial - James Chih Hsin Yang (2018)
Background In the Iressa Pan-ASia Study (IPASS), gefitinib claimed improved progression-free survival (PFS) versus carboplatin-paclitaxel in clinically selected lung cancer patients. The primary objective of this study was to assess the PFS of pemetrexed-cisplatin (PC) followed by gefitinib maintenance versus gefitinib monotherapy in an IPASS-like population. Methods In this open-label, randomised, phase 3 trial, eligible patients were ≥18 years, chemonaïve, East Asian, light ex-smokers/never-smokers with advanced non-squamous non-small cell lung cancer, an Eastern Cooperative Oncology Group (ECOG) performance status 0-1 and unknown epidermal growth factor receptor (EGFR) mutation status who enrolled at 12 sites in Asia. Patients randomly received (1:1) pemetrexed (500 mg/m2) plus cisplatin (75 mg/m2) for six 21-day cycles, followed by gefitinib maintenance or gefitinib monotherapy (250 mg/day). Patient tissue was retrospectively analysed for EGFR mutations. This study is registered with ClinicalTrials.gov, NCT01017874. Findings Between 23rd November 2009 and 27th April 2012, 253 patients entered, and 236 patients were randomly assigned to and treated with PC therapy (N = 114) and gefitinib monotherapy (N = 118). Between-arm baseline characteristics were balanced. PFS was not significantly different between treatment arms (p = 0.217). The unadjusted hazard ratio (HR) was 0.85 (95% confidence interval (CI) 0.63-1.13). The HR should be cautiously interpreted as it was not constant. EGFR mutation status was determined for 74 tissue samples; 50 (67.6%) had mutations. In a pre-specified subgroup analysis, only the treatment-by-EGFR mutation interaction was significant (p = 0.008) for PFS. For the entire treatment period, a higher proportion of patients in the PC/gefitinib arm versus gefitinib experienced possibly drug-related grade 3-4 treatment-emergent adverse events (39 of 114 [34%] versus 19 of 118 [16%]; p = 0.002). Interpretation In the intention-to-treat (ITT) population, PFS was not significantly different. In the biomarker-assessable population, front-line EGFR tyrosine kinase inhibitor monotherapy was not efficacious in patients with wild-type EGFR. Identification of EGFR mutation status is key in the management of advanced non-squamous non-small cell lung cancer. Funding Eli Lilly and Company. © 2014 Elsevier Ltd. All rights reserved.